2012
DOI: 10.1001/archinternmed.2012.1
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Treatment for Socioeconomically Disadvantaged Patients in Primary Care Practice

Abstract: Background Few evidence-based weight loss treatment options exist for medically vulnerable patients in the primary care setting. Methods We conducted a 2-arm, 24-month randomized effectiveness trial in 3 Boston community health centers (from February 1, 2008, through May 2, 2011). Participants were 365 obese patients receiving hypertension treatment (71.2% black, 13.1% Hispanic, 68.5% female, and 32.9% with less than a high school educational level). We randomized participants to usual care or a behavioral i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
181
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(186 citation statements)
references
References 54 publications
(61 reference statements)
4
181
1
Order By: Relevance
“…With few exceptions, 72 most interventions have used a single, predetermined technology and did not give participants the option of choosing between a single or multiple forms of technology simultaneously (which has become commonplace for commercial applications). Most technologies have been created in research settings, although at least 1 published study used a commercially available app.…”
Section: Use Of Mhealth In Weight Management Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…With few exceptions, 72 most interventions have used a single, predetermined technology and did not give participants the option of choosing between a single or multiple forms of technology simultaneously (which has become commonplace for commercial applications). Most technologies have been created in research settings, although at least 1 published study used a commercially available app.…”
Section: Use Of Mhealth In Weight Management Interventionsmentioning
confidence: 99%
“…Indeed, across a large number of studies, weight loss outcomes have been shown to be dependent largely on the level of participant engagement. 63,72 Unfortunately, declining engagement and attrition (often as high as 40%-50%) are characteristic of digital health interventions. 87 Mobile interventions developed in research settings might benefit from leveraging the iterative design and testing conventions that are commonly used in the commercial market to promote user engagement.…”
Section: Gaps and Recommendations For Future Researchmentioning
confidence: 99%
“…However, other studies in the review reported similar use of evidence from theory with a lesser effect (20,31–33). This study also had the highest number of participant–interventionist contacts which may have enabled stronger reinforcement of the behavioural components, and increased participant motivation to lose weight.…”
Section: Discussionmentioning
confidence: 68%
“…The DPP group assessed weight at >3 years, but the intervention continued during those years. Other trials of comparable interventions also intervened until the final assessment [11, 12]. Others who have specifically studied weight loss maintenance performed assessments after continued intervention [13, 14].…”
Section: Discussionmentioning
confidence: 99%